ETHYL METHANESULPHONATE (EMS) INDUCES DROUGHT TOLERANCE IN MAIZE - Dhannoon, Omar M.; Alfalahi, Ayoob O.; Ibrahim, Kadhim M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
THIS STudy was aimed to induce genetic variation toward drought tolerance after treatment with EMS as a mutagen to two maize inbred lines and their single hybrid. The experiment was carried out at Abo-Ghraib Research Station, Baghdad during the spring season of 2019. The experiment included three irrigation intervals 7, 9 and 11, four concentrations of EMS (0, 50, 60, and 70 mM) and three maize genotypes distributed in three replications using randomized complete block design (RCBD) with split-split plot arrangement which included three irrigation intervals 7, 9 and 11 days occupied the main plot, while the sub plots included three maize genotypes, and four EMS concentrations which were distributed in sub-sub plots. Results were revealed significant differences among EMS treatments and irrigation interval treatments. The inbred line 5 in control treatment showed a significant increase in days for both anthesis and silking (70.11 and 71.94) days, respectively. Plants of Nahrain hybrid also showed a super performance in plant height, leaf area, and number of rows ear-1, with a mean of 154.47cm, 746.31cm2 and 17.83 row ear-1, respectively. The irrigation intervals of 9 and 11 days were significantly decreased the mean performance of genotypes, compared to the shortest irrigation interval (7 days) which had highest mean in most traits. None treated plants (0 mM EMS) had a significant effect on the performance of most studied traits, except the anthesis and silking time, which gave the highest values under the concentration 60 mM with 69.11 and 70.48 days, respectively. Hybrid plants interacted significantly with the EMS concentration of 0 mM producing the maximal means of plant height and leaf area (169.56cm and 759.78cm2 respectively). On the other hand, the hybrid was significantly interacted with the shortest irrigation interval in the mean traits of plant's height and leaf area (163.50 cm and 757 cm2, respectively). The triple interaction between hybrids, shortest irrigation interval and EMS concentration of 60 mM had significantly increased leaf area reached 769.67cm2, meanwhile the triple interaction between hybrid plants, shortest irrigation interval, and the EMS concentration of 0 mM recorded the highest value of plant yield (199.67g). It can be concluded from the current study that the genotypes differed in their response to 9 and 11 days irrigation intervals, with a negative effect of the later interval on the vegetative and yield traits of maize compared with shorter irrigation interval.